Псков. История города-крепости - Соломко Наталия Зоревна (Рассказы по истории, 2004)
Экземпляры: М/а ДБ (20101122) / Инвентарный номер: 96768 / Цена: 40.00 / Авт.знак: С 60 / ГРНТИ: 39 / ББК: 26.89(2Рос)